Sheep Beard Disease to Develop Share Factors Impact and Against Fight Measure Events - Hazratkulov, I. A.; Salimov, I. Kh.; Sh, Khakimov (American Journal of Botany and Bioengineering, 2025)
More than 200 species of Clostridia are known, but only a few of them are toxic and pathogenic. Bradzot disease is a very dangerous infectious disease that occurs in the regions of our country. This article describes in detail the etiological factors, epizootological data, clinical signs, pathomorphological changes, diagnostic methods, and preventive measures in the development of Bradzot disease in sheep, based on literature data.